KAJIAN PENGARUH LEBAR ALAS PONDASI ABUTMENT TERHADAP STABILITAS ABUTMENT RENCANA JEMBATAN TELUK BINGKAI KABUPATEN KUTAI KARTANEGARA - Aswan, Dirul (KURVA S JURNAL MAHASISWA, 2014)
Kenohan sub-district is one of the main sub districts in Kutai Kartanegararegency located in the interior Belayan River which is a tributary of theMahakam River. With the geographical conditions traversed by many riversand streams require the construction of a bridge that serves as the supportinginfrastructure of transportation and one of them is a plan to build a bridge inthe village of Teluk Bingkai District of Kenohan.In this study conducted an analysis on the effect of high abutment againstthe bay bridge abutment stability Frame. In this study used two materialspedestal foundation abutment width ratio that is 3,5 meters and 4,5 meters, withthe abutment segment length is 10 meters and the quality of concrete used isK.300. The research result shows that the largest axial force at 11186,52 KN,the lateral force 5875,31 KN and from the calculation shows that the width ofthe foundation abutment pads will affect the ability to resist abutment rollmoment, so the smaller the width of the base, the ability to withstand rollingabutment will be smaller and the need for piles will be more, and vice versawidening the base abutment, it bolsters the ability to withstand the greater andthe need for the stake will be many more. As for the foundation abutment padwidth variation does not significantly affect the ability of withstand slidingabutment.